Implementation of gold investment account from Islamic perspective : studies in Bank Muamalat Malaysia Berhad / Nur Amanina Zulkifli. - Zulkifli, Nur Amanina (2019)
Investment is a way to develop one's property ownership from a sum to a larger amount. Among today's popular investment instruments are investment through gold accounts offered in banks. Investors do not need to store physical gold and indirectly this reduce the risk of theft and loss. In addition, it provides good returns with low risk as the price trend for gold is stable and is always in the higher range for the long term. In Malaysia there are many types of banks that offer gold investment account products, but not all this product is in line with shariah principles. Therefore, this study was conducted at Bank Muamalat Malaysia Berhad (BMMB). From a shariah perspective, the products and techniques of gold investment must follow the Islamic principles and laws, so that the financial activities of the Muslim community do not fall apart from the religious foundation. This study examines the implementation of the gold investment account implemented by BMMB to look at how this product operates and assess its legal validity from an Islamic economic perspective. The study found out that parameters of gold investment which are profit is not guaranteed, avoiding gharar, prohibition of riba and others and BMMB MGi is in accordance with the shariah parameters prescribe by Shariah Advisory Council (SAC) of Bank Negara.